Analisis Hukum Bagi Pekerja Kontrak Yang Di Phk Sebelum Masa Kontrak Berakhir Menurut Undang-Undang Cipta Kerja - Sarbini (Universitas Merdeka Madiun, 2022)
Abstract— The purpose of this study is to determine the legal protection of contract workers in Termination of Employment, to prevent arbitrary termination of employment and to analyze the rights of contract workers who have been subject to Termination of Employment (PHK). The method used in this study uses normative legal research. namely relying on secondary data as the main data source. The conclusion of the analysis of contract workers who are laid off during the contract period must be given their rights while working until the end of the contract, and contract workers can take legal action if their rights are not fulfilled by the employer.